Exceptionally good? Positive experiences of NHS care and treatment surprises lymphoma patients: a qualitative interview study. - Ziebland, S; Evans, J; Toynbee, P (2011)
OBJECTIVE: Initial analysis of an interview study with patients about their experiences of lymphoma identified a strong emergent theme suggesting people were surprised to receive good care in the UK National Health Service. This qualitative analysis helps illuminate the disparity between public perceptions of NHS care and individual experiences. PARTICIPANTS AND SETTING: Forty-one women and men with lymphoma were interviewed at home by an academic social scientist; nine who had had all their treatment before 1997 were excluded from this analysis. DESIGN: Initial qualitative thematic analysis used constant comparison and axial coding. Using narrative analytic methods, we explored how the accounts of positive experiences were structured and framed as well as what was said. RESULTS: Every person we interviewed described positive experiences of the NHS. These included the skills and humanity of the specialist staff involved in their care, the team work, the organization of care and communication and information. However, these positive experiences were often framed as personal good fortune rather than an indication that a high standard might be expected of NHS cancer care. Participants' accounts also suggest a discrepancy through the use of framing devices that imply that less professional, kind and caring treatment might be expected. CONCLUSION: People may be able to maintain the apparently contradictory opinions that the NHS is not very good, even if their own experience of care is excellent, if they construct their own experience as 'lucky'. Health professionals could help by reassuring patients with a more positive, realistic expectation of specialist care.